Pelatihan Sistem Kontrol Lampu Berbasis Bluetoth dengan Arduino Uno Bagi Siswa SMA Xaverius 3 Palembang - Andri Saputra; Yuniansyah Yuniansyah (Lembaga Pengembangan Kinerja Dosen, 2026)
Training on a Bluetooth-based lighting control system with Arduino Uno for students of SMA Xaverius 3 Palembang is one of the community service activities carried out by lecturers from the Palcomtech Institute of Technology and Business and lecturers from Lembah Dempo University. The purpose of this activity is to increase students' knowledge and abilities to utilize Arduino Uno for lighting control. The activity was carried out on Tuesday, November 11, 2025 in Room 3.2 of the Palcomtech Institute of Technology and Business, Palembang. The training was attended by 36 students. The implementation method was carried out by presentation and practice. The training activities were divided into three parts, namely the first presentation about Arduino Uno, the second practice of using Arduino Uno for control, the third exercise by students as an evaluation material to determine the level of understanding of participants. The results of this activity are to increase students' knowledge about Arduino Uno and its various benefits, one of which is for lighting control. This implementation went very well where the training participants actively participated in the activities from the beginning to the end and were able to carry out the exercise on using Arduino Uno for lighting control well and on time, which means that participants could understand the material presented well.